A Novel Technique for Data Steganography - Hindi, A. Y.; Dwairi, M. O.; AlQadi, Z. A. (Engineering, Technology & Applied Science Research, 2019)
In this paper, a novel stego-method will be introduced, which can be used to hide any secret message in any holding color image. The proposed method will be implemented and tested and the calculated parameters will be compared with the LSB method parameters. It will be shown that the proposed method provides a high-security level by using two keys to extract the secret message from the holding image, making it very difficult to hack.